2011
DOI: 10.1073/pnas.1100131108
|View full text |Cite
|
Sign up to set email alerts
|

Control of mTORC1 signaling by the Opitz syndrome protein MID1

Abstract: Mutations in the MID1 gene are causally linked to X-linked Opitz BBB/G syndrome (OS), a congenital disorder that primarily affects the formation of diverse ventral midline structures. The MID1 protein has been shown to function as an E3 ligase targeting the catalytic subunit of protein phosphatase 2A (PP2A-C) for ubiquitinmediated degradation. However, the molecular pathways downstream of the MID1/PP2A axis that are dysregulated in OS and that translate dysfunctional MID1 and elevated levels of PP2A-C into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
65
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 54 publications
4
65
0
Order By: Relevance
“…MID1 mediates binding of the protein complex to the CAG repeat mRNA and acts as a negative regulator of PP2A. MID1 also regulates mTOR activity: in the absence of MID1 PP2Ac binds to its subunits A and Ba (instead of binding MID1 and a4) and then inhibits binding of mTOR to its interacting proteins for example, raptor, which leads to inhibition of mTOR in this protein complex (called TORC1) 19 . Therefore, increased binding of MID1 and S6K to HTT mRNA with elongated CAG repeats leads to an increased protein translation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MID1 mediates binding of the protein complex to the CAG repeat mRNA and acts as a negative regulator of PP2A. MID1 also regulates mTOR activity: in the absence of MID1 PP2Ac binds to its subunits A and Ba (instead of binding MID1 and a4) and then inhibits binding of mTOR to its interacting proteins for example, raptor, which leads to inhibition of mTOR in this protein complex (called TORC1) 19 . Therefore, increased binding of MID1 and S6K to HTT mRNA with elongated CAG repeats leads to an increased protein translation.…”
Section: Discussionmentioning
confidence: 99%
“…MID1 recruits PP2Ac and the translation regulator S6K to these mRNAs. MID1 is a negative regulator of PP2Ac, thereby stimulating mTOR activity, the phosphorylation of S6K, and protein translation 19 . This then would lead to an overproduction of aberrant protein coded by the mRNA and its expanded CAG repeat stretch (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, subsequent studies have shown that in OS the normal regulated turnover of PP2Ac along the microtubules is perturbed, leading to other microtubule-associated proteins being caught in an abnormal phosphorylation state (13), which may affect microtubule polymerization and stability. Recently, mTORC1 signaling, which is also involved in cytoskeletal remodeling, was identified as a downstream component of the Mid1-PP2Ac pathway (35). Further investigation should therefore be focused on elucidating the downstream molecular events triggered by Mid1-directed PP2Ac regulation.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that inhibition/depletion of Mid1 results in the downregulation of mTORC1 signaling (Liu et al, 2011). This report prompted us to examine a new signaling pathway: Rac1-Mid1-mTORC1.…”
Section: Rac3mentioning
confidence: 99%